Dampak Perubahan Teknologi Sistem Logistik di Pelabuhan - Erlisa Aulia; Dhiwa Humaira Ninvika; Yolanda Junitasari; Indah Apsari Asmana Nurfitriani; Siti Sahara (Jurnal Ilmiah Wahana Pendidikan, 2023)
The development and development of industry in Indonesia continues and is now faced with competition in the era of globalization. The development of this industry also occurred in the Indonesian port logistics industry. With the era of globaliasasi, the logistics industry must undergo changes to achieve better goals. One of the changes that occurred was the change in technology to the logistics industry at the port. This research aims to analyze the Impact of Changes in Logistics System Technology in Ports. This research uses Qualitative Descriptive methods with data collection techniques through Literature Studies and data analysis techniques with Inductive Approaches. The results show that the impact of technological changes that occur in the logistics system at the port has a quite positive impact on workers, because it makes it easier for workers to operate ports and is able to compete at the global level and can contribute to lower national logistics costs.